Innovative development of national economies: Collective monograph - Bogdan Grechanyk; Victor Petrenko; Tetiana Ostapenko; Dmytro Onopriienko; Iryna Hrashchenko; Olena Palyvoda; Svitlana Krasniuk; Elvira Danilova; Igor Matyushenko; Valeriy Ryeznikov; Olga Tofaniuk; Olena Khanova; et al. (PC TECHNOLOGY CENTER, 2022)
Collective monograph contains the results of scientific research on topical issues of development of innovation systems at the National level. The problems posed are considered in various aspects, so the results of the research are of practical interest, and their use can contribute to the formation of a policy for the development of regional economies. Section 1 presents the results of a study of the formation processes and features of the functioning of the National Innovation System (NIS), its main components and the links between them. In particular, investment and innovation systems (IIS) are studied as key institutions of the NIS, characterized by a pronounced system-forming function. A block diagram of the National Innovation System has been developed, which includes four main institutional subsystems and subsystems of specific links, which, in fact, ensure the functioning of both institutional subsystems and the entire NIS. The algorithm of their functioning is defined on the basis of its representation by means of a system of inequalities of criterion conditions. Section 2 analyzes the impact of nanoeconomics on the macroeconomics of an individual state based on the characteristics of the nature of nanoeconomics, its tangible and intangible forms, regularities, and evolution. The system of households as cells of individual consumption is characterized and it is shown that the structure of the national economy as part of the service sector, industry and the agro-industrial complex forms an entrepreneurial sector with active individuals. A close relationship has been established between the indicators of the development of nanoeconomics of the macroeconomic situation in a particular country and the relevance of the individual systemic factor for the development of national economic systems has been proved. Section 3 discusses the problem of identifying and leveling the breaks in the innovative development of socio-economic systems on the example of Ukraine in the face of new challenges for the state in the process of developing relations with the EU. An assessment of the level of innovative competitiveness of the Ukrainian economy is made and the most important factors for leveling interruptions in its innovative development in the conditions of association with the EU are identified. Recommendations are given for scheduling breaks in the innovative development of Ukraine. Among them: increased foreign investment and public funding; improvement of legal acts, reduction of corruption, institutional improvement; technology support through regional cluster programs or "smart specialization"; integration into the European Research Area. In Section 4, within the framework of the study of an innovative model of regional management of freshwater resources, environmental priorities, innovative investment dominants, targets and a model of environmentally balanced management of freshwater resources at the regional level are identified. This provides a more objective and balanced assessment of possible schemes and tools for managing the territory's freshwater resources. The conceptual approach presented in the paper is a rather flexible tool with a free choice of elements of analysis depending on the goals and objects of management. The monograph is intended for scientists who study the problems of innovative development of socio-economic systems of national economies either at the level of theoretical approaches, or at the level of practical implementation of measures aimed at determining priority areas for innovative development. It can be useful for practitioners in the field of state regulation, specialists and managers of various levels of industry, agro-industrial complex, services, etc., who solve practical issues of increasing the competitiveness of National Economies. The monograph can also be useful to graduate students and masters of universities in the relevant educational and scientific profile.
Keywords: 300; National innovation system; NIS institutions; Investment and innovation systems; Nanoeconomics; Baby economics; Nanotechnology economics; Breaks in the innovative development; Global Innovation Index; High-tech products; Freshwater resources; Regional management; Innovative model